Light and scanning electron microscopy of the eye of Siganus luridus (Rüppell, 1828) - Derbalah, Amira; El-Gendy, Samir A. A.; Abd-Elhafeez, Hanan H.; Soliman, Soha; El-Mansi, Ahmed A.; Seif, Manal; Rashwan, Ahmed M.; Eldesoqui, Mamdouh B.; Rutland, Catrin Sian; Kubale, Valentina; Alsafy, Mohamed A. M. (Frontiers in Veterinary Science, 2024)
IntroductionThe morphological characteristics of eyes in fishes are highly diverse and have evolved to meet the specific visual requirements as per their habitats. These morphological features of eyes are important for researchers and ecologists. The dusky spinefoot (Siganus luridus) is a tropical teleost fish with a laterally flattened body which lives in the Mediterranean Sea. Currently, there are no histological data relating to the Siganus luridus eye.MethodsIn this study, the morphology of the Siganus luridus eye was examined to enhance our understanding of its structure and its relationship to fish ecology. Detailed gross and microscopic features were recorded using light and scanning microscopy.ResultsThe key observations describe the main structural features of the eye of Siganus luridus, specifically, the diameter of the orbit, architecture of three tunics of eye and detailed lens description. The choroid was divided into four layers, and had a rete mirabile, consisting of numerous small blood vessels in the choroidal gland. The tapetum lucidum was observed, which is interesting since Siganus luridus is herbivore and herbivores typically lack a tapetum lucidum.DiscussionThese observations shed new light on the intricate eye structure of Siganus luridus and provide valuable insights into its visual abilities and adaptations to the aquatic environment and feeding behavior.